2021
DOI: 10.5937/ekonhor2102139e
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of earnings management: The study of Nigerian nonfinancial companies

Abstract: The extant literature links manageress incentives to earnings management. It has globally accounted for the collapse of some well-known, established firms, since it depicts a low financial reporting quality. This study employed data from the 77 nonfinancial firms listed on the Nigerian Stock Exchange for the period 2013-2019 in order to examine the determinants of earnings management. The result showed strong evidence of an incentive to manage earnings. Profitability (Return on Assets - ROA) and the size of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
1
4
0
3
Order By: Relevance
“…A strong positive association was also identified between financial performance, as measured by ROA, and earnings management practices. This finding supports various previous findings (Abu-Jebbeh & Al-Thuneibat, 2017;Emudainohwo, 2021) stating that profitability is closely related to earnings management, but this contradicts previous research that found a negative association between profitability and earnings management (Anjum, Saif, Malik, & Hassan, 2012;Cudia & Dela Cruz, 2018). The finding therefore suggests that management may use DA to control earnings volatility and show consistent profits by reporting a high (or low) profit downward (or upward) (Beaver, 2002).…”
Section: Regressionsupporting
confidence: 79%
See 1 more Smart Citation
“…A strong positive association was also identified between financial performance, as measured by ROA, and earnings management practices. This finding supports various previous findings (Abu-Jebbeh & Al-Thuneibat, 2017;Emudainohwo, 2021) stating that profitability is closely related to earnings management, but this contradicts previous research that found a negative association between profitability and earnings management (Anjum, Saif, Malik, & Hassan, 2012;Cudia & Dela Cruz, 2018). The finding therefore suggests that management may use DA to control earnings volatility and show consistent profits by reporting a high (or low) profit downward (or upward) (Beaver, 2002).…”
Section: Regressionsupporting
confidence: 79%
“…The finding therefore suggests that management may use DA to control earnings volatility and show consistent profits by reporting a high (or low) profit downward (or upward) (Beaver, 2002). Managers tend to manipulate high profits downward to avoid paying high taxes, minimize government scrutiny and to reflect the huge total capital employed in the business (Emudainohwo, 2021).…”
Section: Regressionmentioning
confidence: 92%
“…Manajer adalah yang memiliki paling banyak informasi tentang situasi ekonomi perusahaan. Hal tersebut menimbulkan kesenjangan asimetri informasi antara manajer dengan pemangku kepetingan (Emudainohwo, 2021). Pengungkapan sinyal berupa informasi berkualitas tinggi dapat meningkatkan kredibilitas perusahaan karena dengan demikian manajemen memiliki pandangan yang terencana dan kepercayaan diri akan masa depan perusahaannya (Scott, 2015).…”
Section: Signalling Theoryunclassified
“…Hasil menunjukkan bahwa manajemen dapat melakukan manajemen laba melalui downward laba tinggi ataupun upward laba rendah (Citra et al, 2021). Emudainohwo (2021) mengungkapkan alasannya mungkin untuk mencerminkan modal besar yang digunakan dalam bisnis, menghindari membayar pajak yang besar, dan menghindari pengawasan pemerintah.…”
Section: Pengembangan Hipotesis Kinerja Keuangan Dan Manajemen Labaunclassified
“…The decision to (non)capitalize affects the amount of profit or loss for the period and, consequently, the various indicators based on which the company's performance (see Janeš, 2014, for more detail) is assessed. Managerial judgment does not necessarily lead to managerial opportunism, but different solutions in accounting standards allows managers to choose a more favourable alternative for each situation that arises, thus acting opportunistically (Emudainohwo, 2021).…”
mentioning
confidence: 99%